2017
DOI: 10.1186/s12906-017-1839-4
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic effect of black ginseng extract by augmentation of AMPK protein activity and upregulation of GLUT2 and GLUT4 expression in db/db mice

Abstract: BackgroundBlack ginseng (Panax ginseng C. A. Meyer), three to nine times-steamed and dried ginseng, has biological and pharmacological activities. In this study, the anti-diabetic effects of the black ginseng ethanol extract (GBG05-FF) in typical type 2 diabetic model db/db mice were investigated.MethodsThe effect of GBG05-FF in Type 2 diabetic mice was investigated by their blood analysis, biological mechanism analysis, and histological analysis.ResultsThe mice group treated with GBG05-FF showed decreased fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…AN1284-treated mice exhibited a higher percentage of functional β cells and the ability to secrete insulin than the untreated animals ( Figures 5E,F). One reason for the development of a loss of insulin sensitivity is the downregulation of expression of the GLUT4 transporter, as shown in db/db mice (16). This was demonstrated in the skeletal muscle of the untreated diabetic mice, and GLUT4 mRNA and protein expression levels were improved by AN1284 treatment (Figures 5G,H).…”
Section: An1284 Increases Insulin Sensitivitymentioning
confidence: 73%
“…AN1284-treated mice exhibited a higher percentage of functional β cells and the ability to secrete insulin than the untreated animals ( Figures 5E,F). One reason for the development of a loss of insulin sensitivity is the downregulation of expression of the GLUT4 transporter, as shown in db/db mice (16). This was demonstrated in the skeletal muscle of the untreated diabetic mice, and GLUT4 mRNA and protein expression levels were improved by AN1284 treatment (Figures 5G,H).…”
Section: An1284 Increases Insulin Sensitivitymentioning
confidence: 73%
“…GLUT4 is reported to be decreased in diabetic patients, which leads to a decrease in the uptake/utilization of glucose; whereas, cardiac contractility and metabolism are improved when GLUT4 is upregulated (46). AMPK, a conserved serine/threonine protein kinase, acts as a target for metabolic syndrome prevention (47). In the present study, it was demonstrated that Apelin-13 elevated Apelin-12 expression in serum, myocardial tissues and aortic tissues and resulted in increases in myocardial GLUT4 and p-AMPKα2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a chronic metabolic disorder resulting from insufficient insulin secretion or insulin dysfunction. It may lead to a series of complications such as renal failure, cardiovascular disease, blindness, hypertension, non-alcoholic fatty liver disease (NAFLD), and obesity [ 1 , 2 ]. The global prevalence of DM is on the rise, especially in developing countries [ 3 ].…”
Section: Introductionmentioning
confidence: 99%